Myelodysplastic Syndrome in a Patient With Cronkhite‐Canada Syndrome - Kevin G. Shim; Kevork Khadarian; Jewel Samadder; Jiehao Zhou; Cecilia Arana Yi (Clinical Case Reports)
ABSTRACT Cronkhite‐Canada Syndrome (CCS) is a rare non‐hereditary gastroenterological polyposis syndrome without a clear etiology. Myelodysplastic syndromes (MDS) are clonal hematological disorders. Immune dysregulation has been posited as a contributor to the development of both. A 70‐year‐old man developed chronic diarrhea, dysgeusia, and onycholysis. Endoscopic evaluation and testing to exclude hereditary polyposis syndromes resulted in a diagnosis of CCS. Approximately 1 year later, he was noted to have persistent anemia, which was ultimately diagnosed as MDS. He was evaluated with a myeloid disorder next‐generation sequencing panel and found to have mutations in IDH2, SRSF2, and JAK2. This is the second reported case characterizing concomitant MDS and CCS. This is the first case to report the development of MDS after the diagnosis and treatment of CCS. A successful management strategy for both disorders is outlined within this case report.